The urban lifeworld - Madsen, Peter, 1944-; Plunz, Richard (Routledge, 2002)
Urban conditions are crucial to our experience of modernity, and, as reflected by art, literature and popular culture, have influenced contemporary ideas of what urban life is about.The Urban Lifeworld contributes to our understanding of the cultural role of cities by offering new insight into the analysis of urban experience. Two exceptional cities, New York and Copenhagen, are the focus of this exploration of cultural representations of urban life, which investigates the contrasts between perceptions and formation of the urban lifeworld.Integrating sociological, aesthetic a.